Adsorption and X-ray photoelectron spectroscopy investigation of bisphosphonates on titania and hydroxyapatite surfaces - Dias, Leonardo Francisco Gonçalves [UNESP]; Nakata, Milena Yumi Kasama [UNESP]; Pimentel, Gabriel Junior Cavalcante [UNESP]; Bronze-Uhle, Erika Soares; Mastelaro, Valmor Roberto; Lisboa-Filho, Paulo Noronha [UNESP] (Elsevier, 2023)
This study investigates the adsorption of bisphosphonates (BPs) on TiO2, hydroxyapatite (HA), and TiO2+HA composite surfaces. We first examined the adsorption of these molecules on titania particles and explored the influence of UV irradiation through adsorption curves. Our findings indicate that surface irradiation leads to an increase in the adsorbed BP content due to enhanced BP deprotonation and hydroxyl group generation. Additionally, we evaluated the adsorption of BPs on the TiO2, HA, and TiO2+HA surfaces primarily through X-ray photoelectron spectroscopy (XPS). Our results suggest that BPs adsorb onto TiO2 via a condensation reaction between the BPs and titania surfaces, while phosphate and Ca2+ ions coordinate onto HA surfaces. All functionalized films exhibit a water contact angle of zero. Atomic force microscopy (AFM) measurements show that BP adsorption had less impact on titania topography than HA topography, and mixed films demonstrated behavior similar to that of titania films.
Keywords: Adsorption; Bisphosphonate; Hydroxyapatite; Surface characterization; Titania